Knowledge, attitudes, and capabilities for smoking cessation counselling in dental practice - Yahya, Nurul Asyikin; Saub, Roslan; Md Nor, Mariani (SEAMEO TROPMED Network, 2018)
The Malaysian National Oral Health Plan (2011-2020) recommends dentists advise their patients to stop smoking. Dentists’ attitudes and behaviors can be influenced by variations in clinical practice, whether public or private. We evaluated public and private dentists’ knowledge, attitudes and capabilities for providing smoking cessation counselling in their practices and identify barriers to providing counselling. We conducted a cross sectional study using a self-administered questionnaire among dentists registered in the Dental Practitioners’ Management Information System. Two hundred eighty-five dentists [158 public (53.6%) and 127 private (43.1%) dentists] completed the questionnaire. Significantly more (p<0.35) public (65.1%) than private (51.2%) dentists believed promoting tobacco abstinence is an important part of their professional duty. Significantly more (p<0.001) public dentists (62.0%) than private (37.8%) dentists believed that smoking cessation counselling is an efficient use of clinic time. Significantly more (p=0.006) public (38.6%) than private (21.3%) dentists knew how to assess the patient’s smoking status to formulate a plan to assist the patient in stopping smoking. Significantly more (p=0.04) public (65.8%) than private (74%) stated their clinic has no system to prompt providers to counsel against tobacco use. Significantly more (p<0.001) private (84.3%) than public (51.9%) dentists had no tobacco-related self-help patient education materials in their dental clinic. Public dentists had more knowledge, skills and a positive attitude about providing smoking cessation counselling than private dentists. More public dentists felt they had inadequate time and lack of a support system to follow-up on smoking cessation counselling than private dentists.